Global atmospheric moisture transport associated with precipitation extremes: Mechanisms and climate change impacts. (26th January 2020) - Liu, Bingjun; Tan, Xuezhi; Gan, Thian Y.; Chen, Xiaohong; Lin, Kairong; Lu, Mengqian; Liu, Zhiyong
Abstract: The atmospheric moisture transport processes are of great importance to the occurrence and intensity of precipitation extremes. In this paper, we review the linkage between processes, including the large‐scale atmospheric circulation, atmospheric moisture transport, and extreme precipitation events. We first summarize the thermodynamic and dynamic processes and moisture transport trackings for historical precipitation extremes. We then focus on the contribution of three major atmospheric moisture transport pathways, that is, atmospheric rivers, low‐level jets, and tropical cyclones, to the occurrence and intensity of regional precipitation extremes. Studies on large‐scale atmospheric circulation driving water vapor transport for precipitation extremes over East Asia and North America were specifically reviewed for the understanding of physical mechanisms and predictability of moisture transport and extreme precipitation events. We then pay more attention to the effects of global warming on atmospheric moisture transport, and thus regional precipitation extremes from the perspectives of thermodynamic and dynamic changes of the atmosphere. In the end, we summarize future research challenges on the physical mechanisms of atmospheric moisture transport that are associated with regional precipitation extremes, especially under a warming climate. This article is categorized under: Science of Water > Water Extremes Science of Water > Hydrological Processes Abstract : Physical processes and research schemes for atmospheric moisture transport and their associated synoptic circulation regimes under global warming.